Integrated analysis of multi-omics and fine-mapping reveals a candidate gene regulating pericarp color and flavonoids accumulation in wax gourd (Benincasa hispida) - Xie, Lingling; Wang, Jin; Liu, Feng; Zhou, Huoqiang; Chen, Ying; Pan, Luzhao; Xiao, Wei; Luo, Yin; Mi, Baobin; Sun, Xiaowu; Xiong, Cheng (Frontiers in Plant Science, 2022)
Wax gourd (Benincasa hispida), a popular fruit of the Cucurbitaceae (cucurbits) family, contains many nutrients with health benefits and is widely grown in China and other tropical areas. In this study, a wax gourd mutant hfc12 with light-color pericarp was obtained through ethane methylsulfonate (EMS) mutagenesis. Integrative analysis of the metabolome and transcriptome identified 31 differentially accumulated flavonoids (DAFs; flavonoids or flavonoid glycosides) and 828 differentially expressed genes (DEGs) between the hfc12 mutant and wild-type ‘BWT’. Furthermore, BSA-seq and kompetitive allele specific PCR (KASP) analysis suggested that the light-color pericarp and higher flavonoid content was controlled by a single gene BhiPRR6 (Bhi12M000742), a typical two-component system (TCS) pseudo-response regulator (PRR). Genetic analysis detected only one nonsynonymous mutation (C-T) in the second exon region of the BhiPRR6. Weighted correlation network analysis (WGCNA) identified the downstream target genes of BhiPRR6, probably regulated by light and were intermediated in the regulatory enzyme reaction of flavonoid biosynthetic pathway. Thus, these results speculated that the transcription factor BhiPRR6, interacting with multiple genes, regulates the absorption of light signals and thereby changes the pericarp color and synthesis of flavonoids in wax gourd.